Pengaruh Pengetahuan Perpajakan, Sistem Administrasi Perpajakan Modern Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Pada Kantor Pelayanan Pajak Pratama Jakarta Palmerah - Sumarlin; Yulianto (Jurnal Pajak Vokasi (JUPASI), 2025)
This research is motivated by the suboptimal growth of tax revenue over the past five years (2019-2023), particularly from MSME (Micro, Small, and Medium Enterprises) taxpayers and at the KPP Pratama Jakarta Palmerah. This issue is suspected to be caused by limited tax knowledge, low taxpayer compliance, and insufficient utilization of digital services. Additionally, dishonesty in tax reporting and weak enforcement of tax sanctions have worsened the situation. The lack of digital infrastructure also hinders e-administration, including the tax refund application process. This study aims to analyze the effect of tax knowledge on taxpayer compliance, the effect of the modern tax administration system on taxpayer compliance, the effect of tax sanctions on taxpayer compliance, and determine the combined impact of tax knowledge, the modern tax administration system, and tax sanctions on taxpayer compliance. This research employs a quantitative approach by distributing questionnaires to 100 active MSME taxpayers under the supervision of KPP Pratama Jakarta Palmerah. The results indicate that Tax Knowledge has a positive and significant effect on taxpayer compliance, with an impact of 0.732 or 73.2%. The Modern Tax Administration System also has a positive and significant effect, with an impact of 0.906 or 90.6%. Tax Sanctions positively effect taxpayer compliance, with an impact of 0.791 or 79.1%. Furthermore, Tax Knowledge, the Modern Tax Administration System, and Tax Sanctions collectively have a positive and significant effect on taxpayer compliance, with an impact of 0.938 or 93.8%.